2021
DOI: 10.3389/fphar.2021.618172
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive and Anticancer Property of Selenoproteins in Obese Breast Cancer

Abstract: Obesity is a significant risk factor for various cancers including breast cancer resulting in an increased risk of recurrence as well as morbidity and mortality. Extensive studies on various pathways have been successful in establishing a biological relationship between obesity and breast cancer. The molecular classification of breast cancer includes five groups each having different responses to treatment. Increased levels of inflammatory cytokines seen in obese conditions drive the pro-proliferative pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 145 publications
0
26
0
Order By: Relevance
“…This is consistent with some reports in which it has been determined that obesity is a significant risk factor for various cancers, including breast cancer, resulting in an increased risk, as well as morbidity and mortality. Higher inflammatory cytokine levels during obesity induce the proliferative pathways, such as macrophages infiltration, angiogenesis, and antiapoptotic pathways [ 50 , 51 ]. Adipose tissue generates a chronic low-grade inflammatory state which also contributes to increased oxidative stress [ 8 , 12 ]; it is known that both exercise and MTF reduce adipose tissue and consequently decrease inflammatory state and oxidative stress, and the latter have linked it to an increase in life expectancy [ 13 , 14 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with some reports in which it has been determined that obesity is a significant risk factor for various cancers, including breast cancer, resulting in an increased risk, as well as morbidity and mortality. Higher inflammatory cytokine levels during obesity induce the proliferative pathways, such as macrophages infiltration, angiogenesis, and antiapoptotic pathways [ 50 , 51 ]. Adipose tissue generates a chronic low-grade inflammatory state which also contributes to increased oxidative stress [ 8 , 12 ]; it is known that both exercise and MTF reduce adipose tissue and consequently decrease inflammatory state and oxidative stress, and the latter have linked it to an increase in life expectancy [ 13 , 14 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very recent meta-analysis on 18 case-control studies investigated the relationship between selenium levels in human tissue and breast cancer risk, highlighting a negative correlation [ 90 ]. In this context, a similar study [ 91 ] focusing on breast cancer in obese patients, showed that decreased levels of selenoproteins in the adipose tissue of obese subjects resulted in an inflammatory state that may progress to cancer.…”
Section: Cancermentioning
confidence: 99%
“…The second pathway that was targeted by 93% of the top drugs was the biological oxidation pathway. Increased oxidative stress plays a role in carcinogenesis in breast cancer patients [ 115 ]. In a study of the immune microenvironment of breast cancer, oxidative stress in combination with other biological phenotypes was associated with high immune infiltration [ 116 ].…”
Section: Resultsmentioning
confidence: 99%